2018
DOI: 10.3390/nu11010034
|View full text |Cite
|
Sign up to set email alerts
|

Taste Perception and Caffeine Consumption: An fMRI Study

Abstract: Caffeine is ubiquitous, yet its impact on central taste processing is not well understood. Although there has been considerable research on caffeine’s physiological and cognitive effects, there is a paucity of research investigating the effects of caffeine on taste. Here we used functional magnetic resonance imaging (fMRI) to investigate group differences between caffeine consumers and non-consumers in blood-oxygenation-level-dependent (BOLD) activation during hedonic evaluation of taste. We scanned 14 caffein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 63 publications
1
6
0
1
Order By: Relevance
“…During the hedonic evaluation of caffeine or sucrose, caffeine non-consumers had greater activation in neuronal areas associated with memory and reward, while during the hedonic evaluation of saccharin, greater activation in neuronal areas associated with memory, reward, and information processing occurred in the group of caffeine consumers. The results of the above studies support the observations on differential memory, reward, and information processing of taste between those who habitually consume caffeine and those who do not [50].…”
Section: Caffeine and Taste Perceptionsupporting
confidence: 83%
See 1 more Smart Citation
“…During the hedonic evaluation of caffeine or sucrose, caffeine non-consumers had greater activation in neuronal areas associated with memory and reward, while during the hedonic evaluation of saccharin, greater activation in neuronal areas associated with memory, reward, and information processing occurred in the group of caffeine consumers. The results of the above studies support the observations on differential memory, reward, and information processing of taste between those who habitually consume caffeine and those who do not [50].…”
Section: Caffeine and Taste Perceptionsupporting
confidence: 83%
“…Gramling et al [ 50 ] examined 12 males and 16 females (both caffeine consumers and non-consumers) using functional magnetic resonance imaging (fMRI), and showed differences in blood-oxygenation-level-dependent activation. The study was based on hedonic evaluation of caffeine, sucrose, or saccharin.…”
Section: The Role Of Caffeine In Various Systems In the Human Bodymentioning
confidence: 99%
“…The other network impacted by coffee intake was the limbic network, which is involved in processing the sensory input from the external and internal environment which, by modulating memory and motivation, determine emotional, autonomic, motor, and cognitive responses [45]. A previous resting-state PET study showed reduced metabolic activity in components of this network after caffeine ingestion [18] and a study using a hedonic fMRI task showed decreased activation in neuronal areas associated with memory and reward [46] in caffeine consumers compared to non-consumers; the present FC data are consistent with those reports.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies reported results from sugars and sweeteners separately [ 13 , 17 , 20 , 21 ]. Two of them concluded that sugars elicited responses in more brain regions than sweeteners.…”
Section: Discussionmentioning
confidence: 99%